Frequent nonrandom shifts in the temporal sequence of developmental landmark events during teleost evolutionary diversification. Issue 3 (18th April 2019) - Ito, Fumihiro; Matsumoto, Tomotaka; Hirata, Tatsumi
Abstract: Morphological transformations can be generated by evolutionary changes in the sequence of developmental events. In this study, we examined the evolutionary dynamics of the developmental sequence on a macroevolutionary scale in teleosts. Using the information from previous reports describing the development of 31 species, we extracted the developmental sequences of 19 landmark events involving the formation of phylogenetically conserved body parts; we then inferred ancestral developmental sequences by two different parsimony‐based methods—event‐pairing and continuous analysis. The phylogenetic comparisons of these sequences revealed event‐dependent heterogeneity in the frequency of sequence changes. Most of the sequence changes occurred as exchanges of temporally neighboring events. These heterochronic changes in developmental sequences accumulated along evolutionary time, but the precise distribution of the changes over the teleostean phylogeny remains unclear due to technical limitations.